Effects on post-glacial rebound from the hard rheology in the transition zone - SPADA, GIORGIO; R. SABADINI; D. A. YUEN; Y. RICARD (Geophysical Journal International, 1992)
We analyse the influences of a viscosity increase in the transition zone between 420 and 670 km on the geophysical signatures induced by post-glacial rebound, ranging from the perturbations in the Earth's rotation to the short wavelength features associated with the migration of the peripheral bulge. A self-gravitating model is adopted, consisting of an elastic lithosphere, a three-layer viscoelastic mantle and an inviscid core. The horizontal displacements and velocities and the stress pattern are extremely sensitive to the viscosity increase and to the chemical stratification of the transition zone. The hardening of the upper and the chemical density jumps in mantle below the 420 discontinuity induces a channel effect which contaminates the horizontal deformation both in the near-field and in the far-field from the ice-sheets. These findings indicate that intraplate geodetic data can be used to put bounds on the viscosity increase in the transition zone and on the amount of chemical stratification in the mantle. The stress field induced in the lithosphere by the Pleistocenic ice-sheet disintegration is a very sensitive function of mantle viscosity stratification. The existence of seismic activity along passive continental margins of previously glaciated areas requires a substantial viscosity increase in the mantle, with the viscosity of the transition zone acting as a controlling parameter. A viscously stratified mantle is responsible for a delayed upward migration of stress in the lithosphere which can account for the seismicity today.